Personality Traits, Beliefs, Race or Ethnicity, Language, and Religion as Contributors to Job Discrimination Towards Meranaw Job Applicants - Maunting, Raimah; Guimba, Sonayah (JPAIR Multidisciplinary Research, 2018)
In a highly competitive environment where job-seekers are vying against a pool of equally competent job applicants, the challenge to provide equal employment opportunity against ethnic and racial biases still overshadows the employers’ principle of "merit and fitness." This study focused on the mechanisms of culture such as personality traits, beliefs, race or ethnicity, language, and religion that link to job discrimination among Meranaw job applicants and its implication to personnel management. It attempted to find out the correlation between the profile of the said minorities and the mechanisms of culture that link to job discrimination among them. In this study, the descriptive correlational design was utilized, and a survey was conducted to eighty-seven (87) respondents through the distribution of a researcher-structured questionnaire. By the data gathered, the findings revealed that respondents agreed that mechanisms of culture such as personality traits, beliefs, race or ethnicity, language, and religion contribute to job discrimination among Meranaw job applicants while profile has no significant relationship with most of the mechanisms identified. The study concludes that job discrimination based on culture towards Meranaws does exist, and the devices above of culture have a significant impact on the chance of Meranaw job applicants to be afforded with equal job opportunities in any workplace hierarchy.